Isolated osteoblastoma of the cuboid bone: A case report and review of the literature. (December 2020) - Rovere, Giuseppe; Stramazzo, Leonardo; Pavan, Davide; Cioffi, Alessio; Orlando, Elisabetta; D'Arienzo, Antonio; Capanna, Rodolfo; Maccauro, Giulio; D'Arienzo, Michele; Camarda, Lawrence
Highlights: Osteoblastoma is a locally aggressive, benign, bone-forming tumor. The bones of hand and foot are uncommon localizations. Osteoblastoma of the cuboid bone is extremely rare. Abstract: Osteoblastoma is a relatively rare, benign, bone-forming tumor, commonly observed in the second and third decades of life. Spine and the long tubular bones are the most common sites of involvement. Osteoblastoma is infrequently seen in other sites, including the bones of hand and foot. A rare case of a 35-year-old man that presented an osteoblastoma of the cuboid bone is reported. The patient was treated with surgical resection and grafting. After the intervention, the patient recovered with no clinical and radiological evidence of recurrence after one year of follow-up. Several cases of osteoblastoma-like variant of osteosarcoma of the cuboid have been previously reported, but, to our knowledge, this is the first case of conventional and isolated osteoblastoma involving the cuboid bone reported in the literature.